À propos de Le songe de B. Soares - Chollet, Thibault (Pessoa Plural)
This contribution encapsulates the creative journey of adapting Fernando Pessoa's work into an animated short film, intertwined with personal reflections on inspiration and artistic process. Initially sparked by disillusionment with a previous project and fueled by a deep connection to Pessoa's writings, the filmmaker embarked on a transformative endeavor during daily train commutes. Through meticulous illustration and animation, the film evolved from a solitary pursuit into a poignant expression of existential themes and emotional resonance. Despite challenges and creative detours, the project culminated in a visually rich exploration of melancholy and movement, underscored by an evocative soundtrack.